A Proposed Model For Predicting Financial Tumble And Financial Economics - Al Ethari, Rawaa Yasir Mahdi (Unib Press, 2023)
The study aimed to address the concept of financial and banking defaults and to identify performance indicators and their role in predicting financial defaults in the research sample banks. Developing a standard model consisting of a set of financial ratios capable of distinguishing between troubled banks and non-performing banks. And testing the ability of the proposed model to distinguish between troubled and non-performing banks. Logistic regression model was used to test the research data. The statistical method was used logistic regression analysis to interpret the relationship between a set of variables, and then apply the stepwise selection method through which models can be generated and the best model can be selected from the sum of financial indicators that can be applied and distinguish between troubled and non-performing banks, as the classification related to banks being (in troubled, not in troubled) showed that the total non-performing Iraqi banks are (6) and the non-performing banks are (9) out of the total (15) banks within the years of the research. The study concluded that financial stumbling has a great impact on many parties and parties, as financial stumbling affects the banks themselves as well as the owners and creditors, and it can result in large losses that lead the bank to bankruptcy. This is in addition to the pressures faced by the administration, foremost of which is the relinquishment of the position to a new administration.